Association of the Risk of Childhood Asthma at Age 6 With Maternal Allergic or Immune-Mediated Inflammatory Diseases: A Nationwide Population-Based Study - Yang, Deng-Ho; Chin, Chun-Shih; Chao, Wen-Cheng; Lin, Ching-Heng; Chen, Yun-Wen; Chen, Yi-Hsing; Chen, Hsin-Hua (Frontiers in Medicine, 2021)
Objective This study aimed to assess the associations of the risk for asthma diagnosed at age 6 years or younger in children with maternal immune-mediated inflammatory diseases (IMIDs), including systemic lupus erythematosus (SLE), systemic sclerosis (SSc), inflammatory myositis, rheumatoid arthritis (RA), Sjögren’s syndrome (SS), ankylosing spondylitis (AS), and autoimmune thyroiditis. Methods We identified 628,878 singleton newborns in 2006–2009 who were followed up for at least 6 years. Overall, 153,085 (24.3%) children developed asthma at age 6 years or younger. We examined the associations of the risk of asthma occurring at 6 years or younger in children with maternal IMIDs. Results The risk for asthma was increased in children whose mothers had SLE [odd ratio (OR), 1.13; 95% confidence intervals (CI), 1.00–1.27; p = 0.04], RA (OR, 1.21; 95% CI, 1.07–1.38; p = 0.003), inflammatory myositis (OR, 1.41; 95% CI, 1.12–1.74; p = 0.003), asthma (OR, 1.58; 95% CI, 1.52–1.63), allergic rhinitis (OR, 1.30; 95% CI, 1.28–1.32), or atopic dermatitis (OR, 1.07; 95% CI, 1.02–1.12), but not in those whose mothers had AS (OR, 1.02; 95% CI, 0.87–1.20), SS (OR, 0.96; 95% CI, 0.86–1.07), SSc (OR, 1.28; 95% CI, 0.77–2.14), or autoimmune thyroiditis (OR, 1.01; 95% CI, 0.95–1.07). Other risk factors of childhood asthma included high urbanization level, preterm birth, low birth weight, and maternal use of nonsteroidal anti-inflammatory drugs during pregnancy. Conclusion The risk of childhood asthma at age 6 was increased in children whose mothers had SLE, RA, inflammatory myositis, asthma, allergic rhinitis, and atopic dermatitis.